Definição de metodologias para determinação de ferro em sangue de bovinos resistentes e sensíveis a carrapatos - Pelizaro, Cláudia Bartoli (Universidade Federal de São Carlos, 2007)
Different forms of iron had been determined in the blood of animals with resistance and sensitivity to bovine s ticks. The determined variables were: Iron in total, plasma and serum blood, quantified by flame atomic absorption spectrometry (FAAS); Fe (II), and Fe (III), quantified by spectrophotometry by flow injection analyses; iron freedom through flow dialysis and quantification by g raphite furnace atomic absorption spectrometry (GFAAS); and hematocrit (packed cell volume). The used techniques and the developed methodologies are shown as complementary and adequate for the inquiry of the forms of iron founded in the blood. Blood digestion was not necessary for FAAS total iron determination, avoiding possible contaminations and decreasing the time spending to sample preparation. The Fe(II) and Fe(III) flow injection speciation presented good reproducibility and easy to implement in routine analysis. After freedom iron separation by dialysis membrane, GFAAS allowed the determination of small iron amounts. A statistical study was used for better comparison among the evaluated variables. The t test indicated differences between Canchim and Angus animals resistant and sensible to ticks related to iron amount in the blood s plasma, and in the Fe(III) amount between Angus resistant and sensible animals. In spite of no conclusives, the results indicated a possible tendency related to bovine ticks resistance and iron blood form. With the use of the methodologies defined in the present work, studies with a grater number of animals and small variables could be applied to confirm this hypothesis.
Definition of metodologies for determination of iron in Blood of resistant and sensitive bovine s ticks
Keywords: Química analítica; Sangue; Bovino; Ferro; CIENCIAS EXATAS E DA TERRA::QUIMICA